Class Service for Pregnant Women: Lesson learnt from the Covid-19 Pandemic - Mufdlillah, Mufdlillah; Dwijayanti, Novia; Suryaningsih, Endang Koni (International Journal of Public Health Excellence (IJPHE), 2023)
The maternity class service is a class for pregnant women aimed at educating expecting parents so that they can undergo a healthy pregnancy and delivery process. This study examines the role of midwives in implementing class services for pregnant women during the Covid-19 pandemic. This study uses a qualitative phenomenological approach. Based on the theme, it can be figured out that there are 5 midwives as human resources. All midwives have followed training for pregnant women and have worked with nutritionists, psychiatrists, and doctors. Midwives' roles and responsibilities include providing information on pregnancy, labor, postpartum, and newborn care. The course for expectant mothers is implemented online, and the timing is irregular during the pandemic period; it is only carried out once a week, so there are obstacles in the implementation of the class for pregnant women, that is the delivery process. The midwives should also help delivery process while being the admin of the Bidan Rindu application. Therefore, the provision of information through the application does not run optimally. Overall, midwives' responsibilities in the pregnant women's class program, specifically as presenters and facilitators, are appropriate for implementing services for pregnant women